Medicinal Orchids of Nepal: Are They Well Protected? - Acharya, K.P.; Rokaya, M.B. (Our Nature, 2011)
This paper aims to explore distribution pattern of orchids used for medicinal purpose and their conservation aspect. We compiled information on 82 species of orchids which are used as herbal medicine. Maximum richness of medicinal orchids was observed at an elevation of 1700 msl but, the maximum numbers of protected areas are located at an elevation of 3000 to 3500 msl. There is a negative correlation between number of protected areas and medicinal orchid species richness mentioning that the protected areas are less synchronized with medicinal orchids of Nepal. DOI: 10.3126/on.v8i1.4315